2006
DOI: 10.1529/biophysj.105.067710
|View full text |Cite
|
Sign up to set email alerts
|

Detergent-Resistant, Ceramide-Enriched Domains in Sphingomyelin/Ceramide Bilayers

Abstract: When cell membranes are treated with Triton X-100 or other detergents at 4 degrees C, a nonsolubilized fraction can often be recovered, the "detergent-resistant membranes", that is not found when detergent treatment takes place at 37 degrees C. Detergent-resistant membranes may be related in some cases to membrane "rafts". However, several basic aspects of the formation of detergent-resistant membranes are poorly understood. To answer some of the relevant questions, a simple bilayer composition that would mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
129
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(156 citation statements)
references
References 49 publications
22
129
0
5
Order By: Relevance
“…The importance of ceramide in modulating membrane physical properties and biological function has prompted a number of studies of ceramide incorporation in model membranes. Several recent investigations have examined the effects of ceramide incorporation on coexisting ordered and fluid domains in phase separated binary and ternary lipid mixtures that are used to model membrane rafts Fidorra et al, 2006;Silva et al, 2007;Sot et al, 2006Sot et al, , 2008. This work has demonstrated that ceramide leads to increased membrane heterogeneity and that its effects depend on the membrane composition.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of ceramide in modulating membrane physical properties and biological function has prompted a number of studies of ceramide incorporation in model membranes. Several recent investigations have examined the effects of ceramide incorporation on coexisting ordered and fluid domains in phase separated binary and ternary lipid mixtures that are used to model membrane rafts Fidorra et al, 2006;Silva et al, 2007;Sot et al, 2006Sot et al, , 2008. This work has demonstrated that ceramide leads to increased membrane heterogeneity and that its effects depend on the membrane composition.…”
Section: Introductionmentioning
confidence: 99%
“…The LC (16:0 Cer-enriched) phase observed in monolayers at X 16:0Cer > 0.4 is, in fact, a mixture of two condensed phases (Busto et al 2009). Also, Sot et al (2006) observed domain coexistence over a large region of the egg SM/egg Cer temperature-composition diagram by using calorimetric, fluorescence quenching, and temperaturedependent turbidimetric measurements.…”
Section: Mixtures Of Ceramides With Sphingomyelins and Glycerophosphomentioning
confidence: 95%
“…Cer-induced domain segregation in several lipid mixtures with glycerophospholipids (Huang et al 1996;Carrer and Maggio 1999;Veiga et al 1999;Fanani et al 2002;Hsueh et al 2002;Sot et al 2005Sot et al , 2006Carrer et al 2006) has been reported using different biophysical approaches [see Alonso (2006, 2009) for reviews]. Cers induce high-temperature melting domains in mixtures where phospholipids display low (palmitoyl-oleoyl-PC) (Hsueh et al 2002) and high (dipalmitoyl-PC or dielaidoylphosphatidylethanolamine) (Carrer and Maggio 1999;Sot et al 2005) gel-to-fluid phase transition temperatures.…”
Section: Mixtures Of Ceramides With Sphingomyelins and Glycerophosphomentioning
confidence: 99%
See 2 more Smart Citations